Faktor-faktor yang Berhubungan dengan Kecemasan Anak Prasekolah yang Mengalami Hospitalisasi - Endang ,; Liswaryana , (Pusat Penerbitan Universitas (P2U) Unisba, 2018)
AbstractAn increasing number of children who are hospitalized are at risk of an increase in the population of children who experience anxiety. The purpose of this study was to determine the factors associated with the anxiety of preschoolers who had undergone hospitalization in the children's room at Bangkinang Hospital in 2016. The design used in this study was Analytical with Cross Section design. The sample in this study were preschool children who were treated in the children's room of Bangkinang Hospital totaling 30 respondents with the Total Sampling method. The data collection tool used was a questionnaire with univariate and bivariate analysis. The results showed that there were two factors that influenced anxiety that showed related results: hospital environment p = 0.01 (p 5 0.05), health workers p = 0.006 (p 5 0.05), unrelated, namely family support p = 0.7 (p 5 0.05). It is expected that health workers can provide therapy to children to reduce anxiety.Keywords: Preschoolers, Hospitalisation, Anxiety, Family Support. AbstrakPeningkatan jumlah anak yang dirawat di rumah sakit, beresiko terjadi peningkatan populasi anak yang mengalami kecemasan. Tujuan penelitian ini untuk mengetahui faktor-faktor yang berhubungan dengan kecemasan anak prasekolah yang mengalami hospitalisasi di ruangan anak RSUD Bangkinang tahun 2016. Desain yang digunakan pada penelitian ini adalah Analitik dengan rancangan Cross Sectiona. Sampel dalam penelitian ini adalah anak prasekolah yang dirawat diruangan anak RSUD Bangkinang berjumlah 30 responden dengan metode Total Sampling. Alat pengumpulan data yang digunakan berupa kuesioner dengan analisa univariat dan bivariat. Hasil penelitian menunjukkan dari beberapa faktor yang mempengaruhi kecemasan yang menunjukkan hasil yang berhubungan ada dua: lingkungan rumah sakit p= 0,01 (p ˃ 0,05), tenaga kesehatan p= 0,006 (p ˃ 0,05), yang tidak berhubungan yaitu dukungan keluarga p= 0,7 (p ˃ 0,05). Diharapkan bagi tenaga kesehatan dapat memberikan terapi kepada anak untuk mengurangi kecemasan.Kata Kunci: Anak Prasekolah, Hospitalisai, Kecemasan, Dukungan Keluarga.